IPSR Innovation Profile Brief for “Public Private Partnership to Foster Availability of Forage Seed Mixtures in Tunisia” - M'hamed, Hatem Cheikh; Ben Youssef, Salah; Rekik, Mourad; Frija, Aymen; Idoudi, Zied; Zaiem, Anis; Khorchani, Mohamed Abdelhak; Rudiger, Udo (International Center for Agricultural Research in the Dry Areas, 2023)
In Tunisia, some of the major constraints in crop livestock production systems are monoculture of cereals leading to poor soil health and lack of nutrient rich forages for the key small ruminant activity. Forage seeds were insufficient, and no national seed company had been engaged in forage seed production as this wasn't considered beneficial to them. In 2019, ICARDA and the National Institute of Agronomic Research of Tunisia – INRAT started a facilitation process for a PPP through cooperation and engaging with COTUGRAIN, a private seed production and commercialization company. The partnership is set around the commercialization of some forage crop seeds, in addition to some forage mixtures (Vetch-Oat, Vetch-Triticale, Vetch-Oat - Triticale), pre-defined and advised by the research team composed of INRAT. Different formula for forage seed mixture were tested under different contexts, and recommendations were provided accordingly to the private company COTUGRAIN, to tailor its seed mixtures products for commercialization. More than 150 tons of forage mixture seeds were sold in 2021. More than twenty (20) seed multiplication contracts (forage seeds multiplicator farmers) were established with an area of 300 ha within a three years’ timeframe.